Leisure Travellers in “Old Regime” Naples - Avallone, Paola (TeMA - Journal of Land Use, Mobility and Environment, 2010)
For the pre-unification period, we are still far from the current idea of tourism and, even more, we cannot speak of mass tourism. Tour operators like Thomas Cook arrived in Italy only in the second half of the nineteenth century when the ‘Grand Tour’ was declining. The ‘Grand Tour’, starting from the 17th century, was considered as a long journey across continental Europe made by the wealthy young aristocrats of Britain who intended to complete their education by visiting major cities and sites, with start and finish in the same city. This trip could last from a few months to 8 years. The main destinations were France, Holland, Germany, but it had as a special stage Italy and Rome, and normally included stops in Venice, Florence, Bologna, Pisa and Naples. During the Tour, young people learned about the politics, culture, art and antiquities of European countries. They spent their time sightseeing, studying and making purchases. Italy, with its legacy of ancient Rome, and with its monuments, became one of the most popular places to visit. In addition to knowledge of the ancient world, the British were in contact with the works of Palladio and Neoclassicism. Naples, particularly when it became the capital of Southern Italy with the ascendance of the Bourbon dynasty to the throne, was among the final stages of the ‘Grand Tour’. Besides the natural beauty and the warmth of the mild climate throughout the year, the European cultural elite was interested in the history and art of the southern peninsula. Southern Italy continued the legacy of the Magna Graecia and the influences of the Roman Empire, which could be seen both east and west of the city. But there were also the Vesuvius, the Solfatara, the Campi Flegrei, places related to impressive events and scientifically not understood, which aroused the curiosity of naturalists, scholars of flora and fauna, but also painters and artists. But what were the ways and means of transport to arrive in the Kingdom? Where could travellers refresh? What were the documents that were needed at the border? And again who were they, and where did they stay? The reader may find the answers in the article, which is the outcome of a research of the documents of the time.